THE EFFECT WORK FROM HOME REGULATIONS AND UNEMPLOYMENT RATE ON GOJEK DRIVER WELFARE ONLINE IN CITY OF SURABAYA - Arifin, Syamsul; Utomo, Priyo (2021)
Since its first appearance in China in December 2019, corona virus, also known as Covid 19, has spread fast to practically every corner of earth. At the end of March 2020, it had become epidemic in more than 200 countries in earth with total of infected patients above 800,000 people, Covid-19 was first labeled an epidemic by World Health Organization (WHO) at the end of January 2020. However, due to the virus's rapid spread over the worldwide, the WHO classified Corona Virus a pandemic.. Various ways of handling Covid-19, especially in the hero city of Surabaya, have been carried out starting from the making of policies. One of the methods used to implement social distancing is to work from home or "Work From Home" (WFH). The impact of this policy will certainly have an impact on well-being of online gojek drivers in Surabaya city. The purpose and stages of the research method, the research objective is to reveal the effect of Work From Home, and Unemployment, on well-being of Gojek Online Drivers in the City of Surabaya, the research stages begin with preparation, data collection, data analysis, report preparation and international publication. Derived from findings of research that has been carried out on the effect of Work From Home and the Unemployment Rate on the Welfare of Gojek Drivers in the city of Surabaya, it can be concluded that there is a partial influence and there is also a simultaneous influence.